Navigating the Enigma of Parathyroid Adenoma ‒ a Tale of Diagnosis, Surgery, and Skeletal Symphony - Chakraborty, Agniban; Kumar, Arun; Popli, Vitesh; Ponnam, Ashok Kumar; Goutam, Sidhartha (Lietuvos chirurgija, 2025)
Parathyroid adenomas, though uncommon, can pose significant challenges in diagnosis and management due to their elusive nature. We present a case report of a 47-years old female who presented with a constellation of symptoms indicative of hyperparathyroidism. Initial laboratory investigations revealed elevated serum calcium levels, corroborated by an increased parathyroid hormone (PTH) level. Further imaging studies, including neck ultrasonography and technetium-99m sestamibi scintigraphy, identified a solitary parathyroid adenoma. The patient’s clinical history, coupled with imaging findings, guided surgical approach towards a minimally invasive parathyroidectomy. Histopathological examination of the excised adenoma confirmed the diagnosis, displaying characteristic features of parathyroid tissue hyperplasia. Postoperatively, the patient experienced a rapid normalization of serum calcium and PTH levels, accompanied by a resolution of symptoms. This case underscores the importance of a multidisciplinary approach in the diagnosis and management of parathyroid adenomas, emphasizing the pivotal role of advanced imaging techniques in localizing these elusive lesions. Additionally, it highlights the efficacy of minimally invasive surgical interventions in achieving successful outcomes with reduced morbidity. The presented case contributes to the existing body of knowledge on parathyroid adenomas, providing insights into their clinical presentation, diagnostic challenges, and the significance of timely intervention. Improved awareness and understanding of such cases are crucial for optimizing patient outcomes and refining diagnostic and therapeutic strategies for this rare endocrine disorder.